2013
DOI: 10.4172/2155-6113.1000263
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and Human Immune Deficiency Virus Co-infection in Debre Markos Referral Hospital in Northwest Ethiopia: A Five Years Retrospective Study

Abstract: Background: Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) are major public health problems, especially in Sub-Saharan Africa including Ethiopia. So, updated information on TB-HIV co-infection might be important for the planning, resource allocation, prevention and control activities. Objective: To determine the TB-HIV co-infection and possible associated factors among patients attended TB clinic in five years (2008-2013) at a referral Hospital in Northwest Ethiopia. Methods: A retrospective study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 11 publications
6
14
7
Order By: Relevance
“…Consistent with the global trend, more males (66.6%) than females (33.4%) were diagnosed with TB in this study [1]. The reasons for gender disparity with regards to TB infection is not well understood though it is believed that some cultural and biological factors may play a role [21]. [14] as well as the average rate for Africa (32%) [24].…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with the global trend, more males (66.6%) than females (33.4%) were diagnosed with TB in this study [1]. The reasons for gender disparity with regards to TB infection is not well understood though it is believed that some cultural and biological factors may play a role [21]. [14] as well as the average rate for Africa (32%) [24].…”
Section: Discussionsupporting
confidence: 75%
“…Thus, cumulative incidence of Tuberculosis (21.4%) reported in this study was lower than study done in former capital of Tanzania, Dares Salaam (27.1%) and study done in North west Ethiopia (Debre Markos hospital) (44%) [21]. But, the finding was higher than studies done in Spain and Brazil which were 7.7% [22], and 4.62% [23] respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…The finding of the present study showed that treatment success rate is better than other studies done in University of Gondar Teaching Hospital (60.1%), Debremarkos (59.3%), Gambella (55.7%), Hadiya zones (38%-73%), and Northwest Ethiopia at Felege Hiwot Referral Hospital (26%) [16][17][18][19][20]. The success rate in this study is also higher than studies done in Nigeria [21] and Malawi [22] which have reported success rate as 76.6% and 72% respectively.…”
Section: Discussioncontrasting
confidence: 54%